Gender differences in disability among older adults in the context of social gender and income inequalities: 2013 Brazilian Health Survey - André Luiz Barbosa de Lima; Albert Espelt; Marina Bosque-Prous; Kenio Costa Lima (Associação Brasileira de Pós-Graduação em Saúde Coletiva, 2020)
ABSTRACT: Objectives: To estimate the magnitude of gender differences in disability among adults aged 60 and older and to evaluate whether they can be associated with social gender inequality and socioeconomic contextual factors at the level of Brazilian federative units. Methods: This is a multilevel study that used data from 23,575 older adults of 27 federative units who participated in the 2013 Brazilian Health Survey. The activity limitation index was developed from the item response theory, using activities of daily living and instrumental activities of daily living variables. The association of individual and contextual variables with disability was estimated by assessing the magnitude of differences between genders, using cross-level interaction effects in multilevel generalized linear models, including only the variables that were statistically significant in the final model. Results: The prevalence of disability was higher among women (37.6%) than among men (26.5%), totaling 32.7% of the older adults. In the adjusted multilevel analysis, disability was influenced by income inequality (γgini = 0.022, p < 0.001) among federative units. In addition, gender differences in disability were associated with social gender inequalities (γmgiiXsex = 0.020, p = 0.004). Conclusion: Women had higher disability disadvantages compared to men, and those differences were associated with social gender inequalities among the Brazilian federative units influenced by income inequality.